Strategi Pengembangan Usaha pada Kelompok Petani Tomat di Kabupaten Bandung - Aksa, Azka Azzahra El; Wijaya, Fanji; Aryanti, Asti Nur (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to analyze the business development strategies of tomato farmer groups in Bandung Regency using qualitative methods and a descriptive approach. Primary data was obtained through interviews with farmers, while secondary data came from academic journals and other sources. The SWOT analysis utilized IFE, EFE, IE, and TOWS matrices. Findings indicate that the tomato farming groups in Bandung Regency possess strengths in agricultural infrastructure, plant fertility, soil quality, farmer cooperation, and crop productivity, which can support business success. However, weaknesses include competition with imported products, limited technology and knowledge, fertilizer availability, capital constraints, and weather dependency. External opportunities such as increased agricultural technology adoption, high market demand, research institution support, and training programs can be leveraged to address threats like unstable market prices, climate change, plant diseases, and labor shortages. According to the IE Matrix, the sector is in Quadrant I, indicating internal solid strengths and the ability to capitalize on external opportunities. Recommended strategies include developing and expanding, adopting new technologies, enhancing farmer cooperation, and product diversification to meet growing market demand. Based on the TOWS analysis, the strategies include SO, which leverages internal strengths to seize external opportunities; WO, which uses external opportunities to overcome internal weaknesses; ST, which utilizes internal strengths to counter external threats; and WT, which focuses on mitigating internal weaknesses to reduce the impact of external threats. In conclusion, the tomato farming groups in Bandung Regency have significant potential for success by leveraging internal strengths and market opportunities, though they must address internal weaknesses and external threats.